Kontribusi Kelengkapan Pengisian Formulir Rekonsiliasi Obat terhadap Penggunaan Obat Rasional pada Pasien Rawat Inap di RSU X Bekasi - Hasanah, Kurniatul; Andrajati, Retnosari; Supardi, Sudibyo (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2020)
Drug reconciliation is needed to get rational treatment therapy. The purpose of this study was to analyze the relationship between the completeness of filling out the form of drug reconciliation and rational drug use at Bekasi X Hospital. The study design used a cross-sectional comparative study to compare between 56 completed drug reconciliation forms and 133 incomplete drug reconciliation forms. Sampling is done in total sampling. The research sample that fulfilled the inclusion criteria was 189 forms (40.6%) of all (466) drug reconciliation forms in November 2015-end April 2016 at X Hospital Bekasi. Data was analyzed using Chi-square test. The results showed that the largest percentage of filling out drug reconciliation forms was incomplete (70.4%), carried out by the pharmacist (56.1%) and not signed by a doctor (63.5%). Percentage of rational drug use by 7.9%, with details: correct diagnosis 53.4%, correct indication 53.4%, correct selection of medicine 33.9%, correct dosage 8.5%, exactly how to administer 37.6%, on time giving 13.8% and correct time giving 14.8%. There is no significant relationship between the completeness of filling out the drug reconciliation form, the types of health workers, the presence/absence of a doctor's signature and rational drug use in inpatients (p> 0.05).Tthere is no significant relationship between the completeness of filling out the reconciliation form and rational drug use in inpatients at Bekasi X Hospital (p> 0.05)